SP2.1.8 Informed consent – Are we appropriately assessing the process?. (9th August 2022) - Convie, Liam; Clements, Joshua; McCain, Scott; Campbell, Jeffrey; Clarke, Mike; Kirk, Stephen
Abstract: Aims: There is no standardised measure of the validity of consent. Over 300 million invasive procedures take place globally each year. This study aims to define a core outcome set (COS) for informed consent for therapy. Methods: A prospective mixed method study was undertaken in line with a published protocol and the COS was developed in accordance with Core Outcome Measures in Effectiveness Trials (COMET) methodology. This included a systematic review of outcomes in studies of consent, semi-structured interviews and prioritisation of outcomes using a 2-round modified Delphi technique. Two consensus webinars were used to ratify outcomes for inclusion in the final COS. Results: 36 outcome domains for valid consent were identified and developed by systematic review. 41 semi-structured interviews were conducted with key consent stakeholders (with significant patient involvement) 164 participants from key stakeholder groups across 8 countries completed Delphi Round 1 and 125 completed round 2. 11 of 40 outcomes met the "consensus in" criteria, with 6 meeting "consensus in" in all stakeholder groups. These were included directly in the final COS and the other 5 that met "consensus in" in some but not all stakeholder groups were discussed in consensus webinars. 9 outcomes were defined for the final COS. Conclusion: This is the first study to define a COS for research into informed consent for therapy. It defines what outcomes are most important to all key stakeholders in the consent process and is a step forward in standardising consent research.